A systematic review of targeted social and emotional learning interventions in early childhood education and care settings. Issue 14 (26th October 2021) - Blewitt, Claire; O'Connor, Amanda; Morris, Heather; May, Tamara; Mousa, Aya; Bergmeier, Heidi; Nolan, Andrea; Jackson, Kylie; Barrett, Helen; Skouteris, Helen
ABSTRACT: A growing body of research evidence suggests universal (Tier 1) Social and Emotional Learning (SEL) interventions in early childhood education and care settings can improve children's social and emotional development. Less is known however about the effectiveness of targeted (Tier 2) programmes for preschoolers experiencing social, emotional or behavioural challenges. A systematic literature review was conducted to examine the outcomes associated with targeted (Tier 2) SEL interventions; 19 studies were captured in the review. Findings revealed that while evidence for targeted SEL programming is still emerging, it may offer a promising early intervention approach to strengthen aspects of children's social and behavioural functioning. Based on the evidence reviewed, the impact of targeted SEL intervention on emotional competencies could not be established. Programmes were predominately directed to preschoolers with externalizing problems and there appears to be a dearth of approaches focused on internalizing behaviour. Implications for practice and research are discussed.